Assessment of current Rabies Prevention Act in Japan using infectious disease modelling - Kadowaki, H.; Makita, K.; Hampson, Karen J.; Yamada, A. (Rakuno Gakuen University, 2015)
Purpose:In Japan, rabies has been eradicated in 1957 after introducing current Rabies Prevention Act, and has not occurred ever since. However, vaccination coverage and dog registration stipulated in the act fell dramatically due to the weakened public interest in rabies caused by the long lasted free status from rabies, and it is worth reviewing the risk of rabies transmission under such circumstance. The objective of this study is to predict rabies transmission dynamics in present situation using mathematical modelling.